Bioactive Compounds and Biological Activities of Wild Edible Plant Flowers - Sangsopha, Jintana; Pranil, Thorung; Pumriw, Supaporn; Moongngarm, Anuchita (Burapha Science Journal, 2024)
Background and Objectives: Thailand has a rich biodiversity of wild edible plants, which are important sources of food and medicine in traditional knowledge, due to their nutrient contents and bioactive substances. This research aimed to determine important nutrients, bioactive compounds, and biological activities of flowers from wild edible plants. Methodology: Six species of wild edible plant flowers including Dolichandrone serrulata (DC.) Seem, Senna siamea (Lam.) Irwin & Barneby (cassia), Curcuma sessilis Gage, Curcuma parviflora Wall, Azadirachta indica A.Juss var. siamensis Valeton (neem) and Cratoxylum formosum (Jacq.) Benth. & Hook.f. ex Dyer, were studied. The flower samples were dried and analyzed for the content of nutrients (moisture, protein, fat, carbohydrates, dietary fiber and ash). The dried samples were then extracted with 80% methanol for analysis of bioactive compounds (total phenolic substances and total flavonoid substances) and for biological activity assessments including antioxidant activity (TAC, DPPH, ABTS and FRAP), cytotoxicity to cancer cells (breast cancer cells (MCF-7) and liver cancer cells (HepG2)) and inhibition of a-amylase enzyme and a-glucosidase enzymes. Main Results: Wild edible plant flowers were found to contain high amounts of protein, fiber, and carbohydrates, but were low in fat content. Total phenolic content ranged from 32.34 to 66.53 mg gallic acid equivalents per gram dry weight, with the highest level found in the flowers of Curcuma parviflora Wall. Total flavonoid content ranged from 0.59 to 7.35 mg rutin equivalents per gram of dry weight, and from 2.28 to 27.59 mg quercetin equivalent per gram dry weight with the highest content found in cassia flowers. Cassia flowers had the highest TAC value, neem flowers exhibited the strongest antioxidant activity against DPPH and ABTS radicals, and Cratoxylum formosum flowers had the highest FRAP values. The extracts from neem and cassia flowers also showed the highest toxicity to both breast (MCF-7) and liver cancer cells (HepG2). The neem flower extract possessed the greatest inhibitory effect on activity of the a-amylase enzyme, while cassia flowers showed the highest effect in inhibiting a-glucosidase activity. Conclusions: The six wild edible flower species examined in this study are good sources of nutrients and bioactive compounds, demonstrating antioxidant properties, cytotoxic effects on cancer cells, and the ability to inhibit enzymes associated with the development of diabetes. Notably, Senna siamea (cassia) and Azadirachta indica (neem) showed the greatest potential. This research supports the utilization of these six wild edible flowers as a food source for humans and their application in functional foods and related food products.